Green synthesis of pyrano[2,3-d]pyrimidine scaffolds in cetyltrimethylammonium bromide (CTAB) micellar media - Farzaneh Mohamadpour (Current Research in Green and Sustainable Chemistry)
Cetyltrimethylammonium bromide (CTAB) is used as a catalyst in a green process to produce pyrano[2,3-d]pyrimidine scaffolds using green chemistry techniques. This is achieved by employing an aqueous micellar medium to combine barbituric acid/1,3-dimethylbarbituric acid, malononitrile, and aryl aldehydes in an environmentally friendly manner at 50 °C. This environmentally friendly process is associated with a one-pot, easy accessibility, affordable reaction media, safe reaction conditions, no need for column chromatography for separation, and effective resource use.